In Vitro Activities of the New Antifungal Triazole SCH 56592 against Common and Emerging Yeast Pathogens - Barchiesi, Francesco (American Society for Microbiology, 2000)
A broth microdilution method performed in accordance with the National Committee for Clinical Laboratory Standards guidelines was used to compare the in vitro activity of the new antifungal triazole SCH 56592 (SCH) to that of fluconazole (FLC), itraconazole (ITC), and ketoconazole (KETO) against 257 clinical yeast isolates. They included 220 isolates belonging to 12 different species of Candida, 15 isolates each of Cryptococcus neoformans and Saccharomyces cerevisiae, and seven isolates of Rhodotorula rubra. The MICs of SCH at which 50% (MIC(50)) and 90% (MIC(90)) of the isolates were inhibited were 0.06 and 2.0 μg/ml, respectively. In general, SCH was considerably more active than FLC (MIC(50) and MIC(90) of 1.0 and 64 μg/ml, respectively) and slightly more active than either ITC (MIC(50) and MIC(90) of 0.25 and 2.0 μg/ml, respectively) and KETO (MIC(50) and MIC(90) of 0.125 and 4.0 μg/ml, respectively). Our in vitro data suggest that SCH has significant potential for clinical development.